2002
DOI: 10.1080/13504850110117850
|View full text |Cite
|
Sign up to set email alerts
|

An instrumental variable estimate of the effect of fertility on the labour force participation of married women

Abstract: This study estimates the effect of fertility on the labour force participation of married women in Korea. Since Korean households prefer sons to daughters, there is exogenous variation in the number of children among households, depending on their first child's sex. Using this exogenous variation as an instrumental variable for fertility, it is found that having children reduces the labour force participation of married Korean women by 27.5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
57
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 6 publications
5
57
0
2
Order By: Relevance
“…This is indeed the finding of Chun and Oh (2002) for Korea who use the sex of the first child as an instrument for fertility in a labor supply equation for women, finding that mothers who have an additional child because their first-born child is a girl reduce the probability of labor force participation by 27.5%.…”
supporting
confidence: 55%
“…This is indeed the finding of Chun and Oh (2002) for Korea who use the sex of the first child as an instrument for fertility in a labor supply equation for women, finding that mothers who have an additional child because their first-born child is a girl reduce the probability of labor force participation by 27.5%.…”
supporting
confidence: 55%
“…For example, Rosenzweig and Wolpin (1980) noted that instrumenting endogeneity increases the coefficients compared to the exogenous model (Orbeta, 2005). For Korea, Chun and Oh (2002) found larger coefficient using instrumental variables estimates compared to OLS estimators when using households with at least one child, but smaller instrumental variables estimates when using households with at least two children. In a study of the effect on male labor supply, Lundberg and Rose (2002) also found similar results (Orbeta, 2005).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 85%
“…Different studies used different instrumental variables to generate exogenous variation in fertility. These include, for example, twin first birth (Chun and Oh, 2002;Kim et al, 2009), abortion legislation (Bloom et al, 2007), contraceptive choice of couples (Kim and Aassve, 2006), sibling sex composition (Angrist and Evans, 1998;Cruces and Galiani, 2005), sibling sex composition and contraception unavailability (Aassve and Arpino, 2007) and sex of the first birth (Chun and Oh, 2002;Orbeta, 2005).…”
Section: The Variablesmentioning
confidence: 99%
“…6 Suppose that the government succeeds in suppressing population growth by some policies that do not directly affect household investment in children's education. It might tax childbirth or just legally forbid having more than a certain number of children, like China's one-child policy.…”
Section: Marginal Effects Of Fertility On Investment In Educationmentioning
confidence: 99%